Pesan Dakwah dalam Media Sosial (Analisis Semiotika terhadap Akun Youtube Ustadz Abdul Somad Official): Analisis Semiotika terhadap Akun Youtube Ustadz Abdul Somad Official - Nurhidayah; Umi Halwati; Nawawi (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2023)
This research was conducted to find out the meaning of denotation, connotation, and myths of da'wah messages about the three great sins on Ustadz Abdul Somad's Official Youtube account. The part studied is the contents of Ustadz Abdul Somad Official's YouTube da'wah content. The data was taken from content entitled